Vices, virtues, and consequences : essays in moral and political philosophy - Simpson, Peter, 1951- (Studies in philosophy and the history of philosophy, 2001)
"Vices, Virtues, and Consequences offers a broad study of the basic and universal issues in ethics and politics, the issues of what the human good is and how to attain it and avoid its opposite. These questions have long been debated and are no less debated today. However, according to author Peter Phillips Simpson, within the mainstream of Anglo-American modern philosophy they have been debated too narrowly. This narrowness is one of our modern vices, and it does much to encourage other vices, in particular that of despair of universal and objective reason. The essays in this collection not only attack these vices, but also attempt to replace them with the contrary virtues."--Jacket